In situ electrochemical investigation of the interaction between bacteria Xylella fastidiosa DNA and copper(II) using DNA-electrochemical biosensors - Machini, W.B.S. (2021)
New emerging bacterial plant diseases are spreading fast in different geographical regions, and effective safety measures have not been found. Xylella fastidiosa (Xf) is a Gram-negative bacterial plant pathogen classified as a priority quarantine pest, which affects economically important agricultural crops. Although there is no treatment for diseases caused by Xf, copper-based compounds are widely applied to its hosts. A Xf-DNA-electrochemical biosensor based on bacterial DNA from Xf, is reported here for the first time, and the Cu(II)-Xf-dsDNA interaction was investigated in situ. The Cu(II)-DNA interaction was also evaluated using ctdsDNA-, poly[G]- and poly[A]-electrochemical biosensors. The Cu(II)-Xf-dsDNA interaction occurs by Cu(II) binding at different sites, independent of the bacterial DNA sequence, leading to the condensation/aggregation of Xf-DNA strands due to the formation of a rigid Cu(II)-Xf-dsDNA complex structure. Cu(II) did not cause oxidative DNA damage. Resistance of the bacterial Xf-dsDNA to Cu(II) was observed.